1989
DOI: 10.1128/aac.33.3.331
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of beta-lactams combined with beta-lactamase inhibitors against methicillin-resistant Staphylococcus aureus

Abstract: The effects of combinations of 13-lactams with two P-lactamase inhibitors, sulbactam and clavulanic acid, were determined in vitro against 22 clinical isolates of methicillin-resistant Staphylococcus aureus. Combinations of cefpirome, cefotaxime, and cefazolin with sulbactam (10 ,ug/ml) showed synergistic effects against more than 70% of the strains. Combinations of methicillin and penicillin G with sulbactam also showed synergistic effects against 50 and 68% of the strains, respectively, while cefotiam, moxal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

1990
1990
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 23 publications
1
9
1
Order By: Relevance
“…We determined the clavulanic acid MIC for several strains and found that it varied considerably, from about 8 ,ug/ml (in the laboratory susceptible strains) to as high as 64 p,g/ml or more (for strains CDC 6 [36] and BM 72, for which the methicillin MICs, 4 and 8 ptg/ml, respectively, were also the highest). It appears, therefore, that 4 ,ug of clavulanate per ml may lower the methicillin MIC for some strains through synergistic antibacterial action, similar to the case noted for sulbactam (16) and confirming the findings of Sierra-Madero and colleagues (30).…”
Section: Contributionsupporting
confidence: 74%
“…We determined the clavulanic acid MIC for several strains and found that it varied considerably, from about 8 ,ug/ml (in the laboratory susceptible strains) to as high as 64 p,g/ml or more (for strains CDC 6 [36] and BM 72, for which the methicillin MICs, 4 and 8 ptg/ml, respectively, were also the highest). It appears, therefore, that 4 ,ug of clavulanate per ml may lower the methicillin MIC for some strains through synergistic antibacterial action, similar to the case noted for sulbactam (16) and confirming the findings of Sierra-Madero and colleagues (30).…”
Section: Contributionsupporting
confidence: 74%
“…The variation between inhibitors is presumably due to differences in potency for the 13-1actamase. Contrary to previous reports, synergy was reproducibly observed for some strains with clavulanic acid (11). For cefpirome and methicillin the reduction in MIC was not sufficient to alter the MIC50 or MIC90, although for the individual strains the observed synergy was a greater than four-fold reduction in the MIC of cefpirome.…”
Section: Discussioncontrasting
confidence: 83%
“…Recently, synergistic activity of combinations of fosfomycin with fi-lactams (10,(29)(30)(31)(32) and sulbactam with 13-1aetams (33) has been demonstrated, and for this reason we tested the activity of combinations of meropenem with these antibiotics. The synergism between meropenem and cefpiramide was the greatest among the tested combinations, and this combination also showed effective bactericidal activity against MRSA.…”
Section: Discussionmentioning
confidence: 99%